TEACCH METHOD IN PHYSICAL EDUCATION TO IMPROVE THE PARTICIPATION OF STUDENTS WITH AUTISM SPECTRUM DISORDER - Táboas-Pais, María Inés; García-Marín, Pablo (Revista Conhecimento Online: Diversidade e Inclusão Social, 2025)
The participation of students with autism spectrum disorder in physical education is compromised by difficulties derived from characteristics of this disorder. The Treatment and Education of Autistic and related Communication Handicapped Children (TEACCH) method has been proved effective in improving learning in this group. This article describes a TEACCH-based intervention program that was used to improve the participation and achievement of a male and female student with ASD in physical education lessons. Several strategies were implemented in this program, namely, spatial organization, concept of complete, routines, and visual materials, to achieve this goal. A qualitative case study was conducted, which used participant observation. The results of this study revealed longer motor engagement, lower anxiety, fewer disruptive behaviors, better understanding of lesson dynamics and tasks, and a higher level of autonomy. This study may be used as a reference for physical education professionals to design new programs adapted to each school context.